Calcium/Calmodulin‐Dependent Kinase IV Facilitates the Recruitment of Interleukin‐17–Producing Cells to Target Organs Through the CCR6/CCL20 Axis in Th17 Cell–Driven Inflammatory Diseases. Issue 8 (27th July 2016) - Koga, Tomohiro; Otomo, Kotaro; Mizui, Masayuki; Yoshida, Nobuya; Umeda, Masataka; Ichinose, Kunihiro; Kawakami, Atsushi; Tsokos, George C.
Abstract : Objective: The recruitment of interleukin‐17 (IL‐17)–producing T helper (Th17) cells to inflammatory sites has been implicated in the development of organ damage in inflammatory and autoimmune diseases including systemic lupus erythematosus (SLE). To define the mechanism of calcium/calmodulin‐dependent kinase IV (CaMKIV) activation of Th17 cell recruitment to target tissues, we performed anti–glomerular basement membrane antibody–induced glomerulonephritis (AIGN) experiments in mice and studied samples from patients with SLE. Methods: We induced experimental AIGN in CaMKIV‐sufficient or CaMKIV‐deficient mice and compared histology, Th17 cell–related chemokine expression, and numbers of IL‐17–producing cells in kidneys. We also evaluated the efficacy of the CaMKIV inhibitor KN‐93 in AIGN‐induced kidney disease. The expression of CCR6 in memory CD4+ T cells before AIGN induction was analyzed by flow cytometry. We investigated the correlation between CCR6 expression in peripheral blood and the severity of glomerulonephritis in patients with SLE. Results: CaMKIV‐deficient mice displayed less glomerular injury after induction of AIGN. Kidney infiltration by IL‐17–producing CD4+ T cells along with CCR6 and CCL20 expression were significantly decreased in CaMKIV‐deficient mice. Similarly, treatment of mice with KN‐93 improved clinical and pathologic outcomes. Expression and function of CCR6 in peripheral blood memory CD4+ T cells was decreased in CaMKIV‐deficient mice. Expression of CCR6 correlated positively with severity of organ damage in SLE patients. Conclusion: CaMKIV inhibition represents a novel therapeutic strategy for treatment of Th17 cell–mediated tissue damage in inflammatory diseases.